Dance and the lived body : a descriptive aesthetics - Fraleigh, Sondra Horton, 1939- (University of Pittsburgh Press Digital Editions., 1987)
" ... examines and describes dance through her consciousness of dance as an art, through the experience of dancing, and through the existential and phenomenological literature on the lived body. She describes, with performance photographs, specific imagery in dance masterworks by Doris Humphrey, Anna Sokolow, Viola Farber, Nina Weiner, and Garth Fagan."--Publisher